The problem of ensuring requirements for microaccelerations on board of small spacecraft - A. V. Sedelnikov; E. V. Eskina; A. S. Taneeva; E. S. Khnyryova; E. S. Matveeva (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper provides an overview of ways to reduce micro-accelerations in the internal environment of a small spacecraft and provides quantitative estimates of the level micro-accelerations. The design image of a small technological spacecraft is being formed. The issues of ensuring the quality of the obtained results of gravity-sensitive processes by monitoring the level of micro-accelerations on board small spacecraft are considered. The results obtained can be used in the design and operation of small spacecraft for technological purposes.